Loss of Anterior Gradient-2 expression is an independent prognostic factor in colorectal carcinomas - Riener, Marc-Oliver; Weichert, Wilko (European journal of cancer, 2014)
Aims - The human Anterior Gradient-2 (AGR2) protein is strongly expressed in various human cancers, and it has been described to promote aggressive tumour features in some entities. So far, a comprehensive analysis of AGR2 expression in colorectal carcinomas has not been described. - Methods - Normal intestinal cells and colorectal carcinoma cell lines were analysed for AGR2 expression. AGR2 protein expression was immunohistochemically analysed in 28 normal tissue samples and 1068 tissue samples of clinically well characterised colorectal carcinomas. For statistical analysis, chi square test, spearman rank correlations, Kaplan-Meier estimates (Log rank test) and Cox regression were applied to test for diagnostic or prognostic associations. - Results - In the normal intestinal cell line and in normal colon mucosa AGR2 was found in all cases (n=28). In contrast, loss of AGR2 was found in all six analysed colorectal cancer cell lines and in 833/1068 (78%) of the colorectal carcinoma tissue samples analysed, and it was significantly associated with a higher tumour grade and tumour localisation in the left-sided colon. In addition to the conventional prognostic tumour parameters pT category, nodal status, metastasis and histological tumour grade the loss of AGR2 expression was significantly associated with reduced overall survival times in univariate and multivariate analyses, thus suggesting AGR2 as an independent prognostic factor in primary colorectal carcinoma. - Conclusions - AGR2 is frequently lost in colorectal carcinomas and might be a novel independent prognostic factor for overall patient survival.